(untitled) (Research, Society and Development, 2020)
Comminuted mandible fractures (CMF) are fractures that have multiple fracture lines resulting in several bone fragments. Among the forms of treatment for this type of fracture, open reduction with rigid internal fixation (RIF) seems to be the best option. This paper aims to report two cases of comminuted mandibular fracture treated by open reduction, simplification, and rigid internal fixation. In both cases, the fracture was simplified with 1.5mm miniplates and after the anatomy was restored, a 2.4mm reconstruction plate and bicortical anchor screws were installed. This type of approach provides stable occlusion, reconstruction of the mandibular anatomy and the absence of loose fragments that could progress to infection. It is concluded that the open reduction and the RIF of comminuted fractures using the principle of simplification optimizes the results and reduces complications.